К вопросу об участии армянской торговой буржуазии Ирана в ирано-русских торгово-экономических и политических отношениях в XVII веке - Байбуртян, Ваган (ՀՀ ԳԱԱ հրատ.)
«Հյուսիսային ճանապարհի» և Վոլգա-Կասպյան մայրուղու բացումից հետո եվրոպական համարյա բոլոր առաջատար պետությունները սկսում են եռանդուն ջանքեր գործադրել, որպեսզի ստանան ռուսական պետության վրայով Իրանի հետ առևտրի մենաշնորհը։ Սակայն Ռուսաստանը վարում էր իր առևտրականներին հովանավորելու քաղաքականություն: In 1660 Khoja Zakar Sharimanian, a representative of the New Julfa Armenian Trade Company, arrived in Moscow from Isfahan. It is clear that Shah had provided Sharimanian with certain degree of autority. In Moscow, he played the role of diplomatic envoy, mandated to normalize Iran’s relations with Russia. The Armenian Trade Company and also the Safavid government mandated him to the test the government’s feeling, regarding the signing of a trade agreement.
Keywords: История